Financialisation, West European banking groups and postsocialist transformation in East-Central Europe: Geographies of subnational banking in Croatia - Benceković, Sara (Trinity College Dublin. School of Natural Sciences. Discipline of Geography, 2024)
The overarching aim of this dissertation is to examine the main drivers and manifestations of financialisation in the East-Central European periphery after the collapse of state socialism. To do this, the dissertation takes Croatia as a case study and delves into the role of West European banks in transforming the banking sector at the subnational level. In particular, the dissertation addresses the following main questions: ‘How have West European banks managed to 'penetrate' postsocialist Croatia and how has this transformed Croatian banking’; ‘How do West European banking groups organise their retail banking operations in Croatia’, and ‘What lending strategies do West European banking groups pursue across the country’. The dissertation adopts a mixed-method approach to studying the selected case study of West European banking groups in Croatia. The geocoding methods were adopted to trace the branch locations and flows. More specifically, the Geographic Information System (GIS) and spatial analysis are used to capture, analyse, and present the data on the West European bank branch network in Croatia. The quantitative data is supplemented by multi-method qualitative approaches, namely, document review and interviewing. The relevant qualitative information is primarily obtained via elite and expert interviews with bankers, financial experts, and the officials at the Croatian Central Bank, as well as through the analysis of banks’ balance sheets and financial reports. The dissertation's central argument is that integrating the Croatian domestic banking system into European and global ‘financial chains’ has been an intrinsically uneven process, which fragmented subnational banking geographies and contributed to increasing inequality across regions. Accordingly, the dissertation finds that, first, mid-tier, West European banks, primarily from geographically proximate countries of Italy and Austria, penetrated the region by exploiting the local financial crises that followed the fall of the socialist regime, often choosing to purchase existing, well-established banks. In doing so, the West European banks established a radically different financial regime than the one that existed prior to their entry, as they transformed the Croatian banking landscape into a shareholder-oriented, distantly governed, highly concentrated, and homogenous financial system dependent on parent bank structures. Second, the transformation of Croatian banking is reflected in the resultant reorganisation of retail banking operations, as the bank branch network shrunk and abandoned previous agro-industrial regions for coastal tourism regions, influenced by the changing earning logic from productive to asset-price-based profit. Finally, following the new financial logic, banks refocused their lending strategies towards households and, above all, housing with state subsidies, thus establishing an important financial chain between the state, parent banks, and households, through which the value flows from states and households towards foreign parent banks. This redirected lending towards regions where real estate is expected to appreciate, such as coastal tourism regions, which deepens existing regional inequalities between regions and creates new imbalances with the changing economic structure of the country. The research concludes that the rise of financialisation driven by West European banks has been a critical force in shaping and deepening patterns of geographic inequality in Croatia. Specifically, while some regions grew from FDI and access to credit, others lagged behind, increasing the economic gap between them. In broad terms, the dissertation contributes to understanding how the expansion of West European banks in East-Central Europa and the integration into financial chains has shaped the financial system in these countries, increasing regional asymmetries and systemic economic vulnerability.
APPROVED
Keywords: Financialisation, West European banks, banking geographies, East-Central Europe